The Impact of Academic Stress and Cyberloafing on Students’ Smartphone Addiction - Sriwahyuningsih, Vera; Barseli, Mufadhal (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2023)
This research is motivated by the high level of smartphone addiction among students. This is due to the coping activities carried out as a form of release from academic stress experienced by students. One of these coping activities is cyberloafing behavior. This study aims to determine the impact of academic stress and cyberloafing on smartphone addiction. This study is quantitative research with multiple regression analysis. The population in this study were 319 students of class XI SMA N 4 Padang, and the sample size was 177 people using the Proportional Random Sampling technique. The data was collected using an academic stress instrument. The results of the validity and reliability test of the academic stress instrument adapted from the SSA scale (Academic Stress Scale) were declared valid and reliable. Data were analysed with descriptive statistics and multiple regression. The results of this study indicate that academic stress and cyberloafing together have a significant impact on smartphone addiction. This means that the higher the level of academic stress experienced by students and the higher the cyberloafing carried out, the higher the level of smartphone addiction by students. This finding can be a reference for counselling teachers to provide services in reducing academic stress and reducing the level of cyberloafing and smartphone addiction in students.